Applying Computer Assisted Language Learning to Improve English Vocabulary Mastery through Multimedia Fun Vocabulary for Elementary Students - Eka Surya Fitriani; Virdyra Tasril; Ade Rizka; Siti Dewi Murni (Universitas Muhammadiyah Semarang, 2023)
There have been developments of multimedia language learning after Covid Pandemic. Many elementary schools have applied Computer Assisted Language Learning to overcome the process of learning vocabulary at class. Hence this study was conducted in purpose to see the use of multimedia and to improve the vocabulary mastery of grade IV elementary students in Kelambir V Kebun by implementing interactive designed multimedia called Fun Vocabulary. Applying qualitative research method, this study measured the users’ evaluation on multimedia and pretest-posttest result. The development was carried out within five phases, i.e.: (1) Analysis, (2) Design, (3) Development, (4) Evaluation, and (5) Implementation. The subjects were the grade IV students of elementary students in Kelambir V Kebun. The instruments used in data collection were students’ questionnaire and pretest-posttest. The result of the study showed that: (1) the usefulness of multimedia Fun Vocabulary was in good category with the average score of the quality of the program in terms of students’ evaluation of 4.1; and (2) there is an improvement between the average score of pretest (60) and posttest (82). As a result, this multimedia was appropriate and applicable for students to learning English at the class.